rAAV expressing recombinant antibody for emergency prevention and long-term prophylaxis of COVID-19 - Esmagambetov, Ilias B.; Ryabova, Ekaterina I.; Derkaev, Artem A.; Shcheblyakov, Dmitry V.; Dolzhikova, Inna V.; Favorskaya, Irina A.; Grousova, Daria M.; Dovgiy, Mikhail A.; Prokofiev, Vladimir V.; Gosudarev, Andrey I.; Byrikhina, Daria V.; Zorkov, Ilia D.; et al. (Frontiers in Immunology, 2023)
Numerous agents for prophylaxis of SARS-CoV-2-induced diseases are currently registered for the clinical use. Formation of the immunity happens within several weeks following vaccine administration which is their key disadvantage. In contrast, drugs based on monoclonal antibodies, enable rapid passive immunization and therefore can be used for emergency pre- and post-exposure prophylaxis of COVID-19. However rapid elimination of antibody-based drugs from the circulation limits their usage for prolonged pre-exposure prophylaxis. In current work we developed a recombinant adeno-associated viral vector (rAAV), expressing a SARS-CoV-2 spike receptor-binding domain (RBD)-specific antibody P2C5 fused with a human IgG1 Fc fragment (P2C5-Fc). A P2C5-Fc antibody expressed by a proposed rAAV (rAAV-P2C5-Fc) was shown to circulate within more than 300 days in blood of transduced mice and protect animals from lethal SARS-CoV-2 virus (B.1.1.1 and Omicron BA.5 variants) lethal dose of 10^5 TCID50. In addition, rAAV-P2C5-Fc demonstrated 100% protective activity as emergency prevention and long-term prophylaxis, respectively. It was also demonstrated that high titers of neutralizing antibodies to the SARS-CoV-2 virus were detected in the blood serum of animals that received rAAV-P2C5-Fc for more than 10 months from the moment of administration. Our data therefore indicate applicability of an rAAV for passive immunization and induction of a rapid long-term protection against various SARS-CoV-2 variants.